2014
DOI: 10.5901/mjss.2014.v5n8p312
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Competency in the Teaching and Learning of Chemistry Practical

Abstract: This study aims to explore the contribution of teachers ' competency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
2
20
0
3
Order By: Relevance
“…Motivation and enhancement were thus identified as key in pushing and encouraging nursing students to achieve success, confirming Copriady, [25] who concluded that instructors' competency is related to how teachers influenced students through motivating and influencing them by fostering positive attitudes to learning and providing appropriate feedback on their learning activities. Moreover, Shah [18] illustrated that the competences of faculty staff to motivate students to learn and develop supportive relationships positively affected students' values and shaped their attitudes.…”
Section: Part I: What Is the Level Of Professionalism Among Faculty Mmentioning
confidence: 63%
See 1 more Smart Citation
“…Motivation and enhancement were thus identified as key in pushing and encouraging nursing students to achieve success, confirming Copriady, [25] who concluded that instructors' competency is related to how teachers influenced students through motivating and influencing them by fostering positive attitudes to learning and providing appropriate feedback on their learning activities. Moreover, Shah [18] illustrated that the competences of faculty staff to motivate students to learn and develop supportive relationships positively affected students' values and shaped their attitudes.…”
Section: Part I: What Is the Level Of Professionalism Among Faculty Mmentioning
confidence: 63%
“…Performance skills such as vocalization, eye contact, being spatially aware and a teacher's obvious display of passion were cited as examples of this. Copriady [25] pointed out that abilities and competencies in more traditional pedagogical tasks such as developing instructions, lesson planning, preparing, implementing and translating the process in the form of continuous assessment and feedback throughout the teaching process in the theory and laboratory is more important.…”
Section: Part I: What Is the Level Of Professionalism Among Faculty Mmentioning
confidence: 99%
“…These findings also collaborated the view of Omotere (2011) who was of the view that impact of teachers' teaching method played significant roles in the competency and productivity levels of the teachers and eventually make learning more permanently in the learners. In similar vein, Adesina (2012), Copriady (2014) as well as Popoola (2014) equally reiterated the effectiveness of teachers' use of instructional method in the attainment of educational goals at all levels of educational system. This will eventually pave way for teacher competencies in their various aspects of their disciplines.…”
Section: Discussionmentioning
confidence: 95%
“…Simply put, teachers need to possess all the necessary elements of competency to provide quality teachings for their students (Saedah & Mohammed Sani, 2012). Furthermore, teachers' competency in preparing quality lesson plans is also an essential factor in determining the success of a teaching session (Copriady, 2014). Clearly, teaching competency encompasses a host of factors, including the planning, implementation, and evaluation of school curriculum and standards, which together will have a huge impact on the quality of teaching (Yu, Luo, Sun, & Strobel, 2012).…”
Section: Problem Statementmentioning
confidence: 99%